Internationalization of born-global firm: The case of two Chinese SMEs - Zhang, Xi (My University, 2006)
The phenomenon of born-global firms has been studied for a decade. Attribute to many changes in the business environment, such as globalization of markets and increasing global niche markets, as well as the development of high technology in communication and transportation, the born-global firms emerge worldwide and challenge the traditional internationalization models by adopting a global approach shortly or right from their inception. This study seeks to uncover the specific orientations and strategies that mostly characterize the born-global firms, and how do these factors and strategies interrelate with each other and accelerate the internationalization of born-global firms. In current born-global phenomenon research, many theories explain the rapid internationalization differently. Resource-based theory addresses born-global firms leverage a collection of fundamental intangible resources comprising a specific constellation of marketing orientations and strategies. The intangible resources such as knowledge, skill and experience that foster unique products allow born-global firms to serve niche markets well. Network theory argues born-global firms leverage competence of the partners to overcome the resource scarcity, serve the existing market and explore the potential business opportunities. Entrepreneurship theory holds that the rapid internationalization of born-global firms is associated with the entrepreneur’s characteristics. The entrepreneur’s initial international ambition, the prior knowledge and work experience has an important influence on the behaviour of born-global firms and accelerate their internationalization. Based on these theories, in the empirical part, the internationalization of born-global firms is analyzed through three dimensions, namely entrepreneurial characteristics, global orientation, and distinctive marketing strategies. The empirical part was conducted through a qualitative, multiple-case-based research method by examining and investigating the rapid export performance of the two export-involved Chinese born-global firms. The empirical results support the proposed factors and strategies. Findings support the rapid internationalization is driven by entrepreneur’s characteristics, global orientation and distinctive marketing strategies. In brief, firstly, the founding entrepreneurs have great influence on companies’ rapid internationalization, especially their knowledge, experience and personal network are crucial prerequisites; secondly, companies have explicit global orientation from inception; thirdly, the companies are well aware of the niche market and serve the market either by product differentiation focus or quality focus; and finally, companies leverage the founder’s knowledge, networks and competence of the foreign distributors a lot to overcome their tangible resource scarcity.
Keywords: born-global firm; internationalization; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|